1993
DOI: 10.1152/jappl.1993.75.3.1354
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training alters endothelium-dependent vasoreactivity of rat abdominal aorta

Abstract: We tested the hypothesis that adaptations in peripheral arterial vasoreactivity are induced by exercise training. Male rats were trained to run on a treadmill at 30 m/min (15 degrees incline) for 1 h/day 5 days/wk for 10-12 wk. Efficacy was indicated by a 51% increase (P < 0.05) in citrate synthase activity in soleus muscle of exercise-trained (ET) rats compared with that of sedentary (SED) control rats. Responses to vasoactive compounds were examined in vitro using rings of abdominal aorta. Maximal isometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
3
7

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 14 publications
16
173
3
7
Order By: Relevance
“…We (Delp et al 1995, McAllister et al 2000 and others (Vargas et al 1995) have found endothelium-dependent dilation of rat vasculature to be blunted in hypothyroidism; conversely, we (McAllister et al 1998(McAllister et al , 2000 and others (Scivoletto et al 1986, Vargas et al 1995, Honda et al 2000 have observed augmented endothelium-dependent vasodilation in the hyperthyroid state. Since a primary mediator of endothelium-dependent dilation in vasculature of the rat is NO (Delp et al 1993), our findings collectively suggest that alterations in endothelium-dependent vasodilation with changes in thyroid status are, in part, accounted for by an altered capacity for NO formation. It is clear, however, that changes in NO formation do not solely account for altered endothelium-dependent vasodilation.…”
Section: Capacity For No Formationmentioning
confidence: 56%
See 1 more Smart Citation
“…We (Delp et al 1995, McAllister et al 2000 and others (Vargas et al 1995) have found endothelium-dependent dilation of rat vasculature to be blunted in hypothyroidism; conversely, we (McAllister et al 1998(McAllister et al , 2000 and others (Scivoletto et al 1986, Vargas et al 1995, Honda et al 2000 have observed augmented endothelium-dependent vasodilation in the hyperthyroid state. Since a primary mediator of endothelium-dependent dilation in vasculature of the rat is NO (Delp et al 1993), our findings collectively suggest that alterations in endothelium-dependent vasodilation with changes in thyroid status are, in part, accounted for by an altered capacity for NO formation. It is clear, however, that changes in NO formation do not solely account for altered endothelium-dependent vasodilation.…”
Section: Capacity For No Formationmentioning
confidence: 56%
“…Collectively, these findings suggest that thyroid status primarily affects the vascular endothelium. Endotheliumdependent dilation of the rat aorta is primarily mediated by nitric oxide (NO) (Delp et al 1993). We therefore hypothesized that altered endothelium-dependent vasodilation with changes in thyroid status is due to changes in the capacity for NO formation, as reflected by NO synthase (NOS) activity.…”
Section: Introductionmentioning
confidence: 99%
“…†P < 0.05 CON versus EX. Delp & Laughlin, 1997;Delp et al 1993), but not short-term (1 day to 2 weeks; Delp & Laughlin, 1997), treadmill running in rats increases the maximal responsiveness of abdominal aortic rings to acetylcholine. In a recent study training (10-12 weeks treadmill running) did not alter the dilatation in response to acetylcholine of isolated rat soleus feed arteries (Jasperse & Laughlin, 1999).…”
Section: Relaxation Responsesmentioning
confidence: 94%
“…87,88 Higashi et al had shown that long-term physical exercise improved endothelium-dependent vasorelaxation through an increase in the release of NO in normotensive and hypertensive subjects. 89 Exercise training for only four weeks has been shown to increase basal nitric oxide production in hypercholesterolaemic patients, independent of lipid profile modification.…”
mentioning
confidence: 99%